Kebijakan Penerapan Penanggulangan Kejahatan Money Politic Melalui Hukum Pidana Dalam Penyelenggaraan Pemilihan Kepala Daerah yang Demokratis - Budi Rahman (CV. ITTC INDONESIA, 2023)
One of the challenges in elections is the rampant practice of money politics that takes place at almost all levels of elections and money politics is one of the factors causing high-cost democracy; The modus operandi/forms of money politics include: Distribution of money to voters; Distribution of sarong/cement/sugar and coffee/hijab/peci; The criminal responsibility for political money crimes is in accordance with Article 187 A paragraph (1) and paragraph (2) of Law Number 10 of 2016 concerning Amendments to Law Number 1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents, and Mayors into Law, which is punishable with a prison sentence of not less than 36 (thirty-six) months and a maximum of 72 (seventy-two) months and a fine of at least Rp200,000,000.00 (two hundred million rupiah) and a maximum of Rp1,000,000,000.00 (one billion rupiah).